Pengaruh Pengetahuan Auditor, Pengalaman Auditor, dan Tekanan Ketaatan Terhadap Audit Judgment pada Kantor Akuntan Publik di Kota Medan - Krishna Wati; Desnitar Manao; Irene Srimawati Doloksaribu; Wilsa Road B Sitepu (Politeknik Ganesha Medan, 2021)
In making the right judgment, the public accountant must have a lot of knowledge and experience so that when assessing an entity, the decisions made are not wrong. And in making decisions, it should not be influenced by the entity or its own superiors. There is a case in 2018 that happened to two public accountants who did not understand how to take the right judgment in carrying out the task of auditing the annual report to PT Sunprima Nusantara Financing (SNP Finance). Based on this case, this research aims to analyze the making of audit judgment in the city of Medan. It must be influenced by the existence of knowledge, experience and obedience pressure so that cases like the above do not occur in the city of Medan. In collecting the questionnaire data using a Likert scale and choosing multiple linear regression analysis as a research hypothesis testing. The results showed that the determination coefficient test resulted in a percentage of 54% with the conclusion that audit judgment can be explained by auditor knowledge, auditor experience, and pressure.